1993
DOI: 10.3109/02841869309083915
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Analogue Phase I Trials in Neuroendocrine Neoplasms

Abstract: To further investigate the antineoplastic efficacy and safety of somatostatin analogues, 2 trials were performed. Octreotide, SMS 201-995 (Sandostatin), was escalated in doses ranging from 1,500 micrograms to 6,000 micrograms daily in 14 patients with carcinoid. Somatuline, (BIM 23014C, Angiopeptin, Lanreotide) was given in doses ranging from 2,250 micrograms to 9,000 micrograms daily to 13 neuroendocrine patients (6 carcinoid, 2 atypical carcinoid, 3 pancreatic islet cell and 2 small cell lung cancer patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 14 publications
2
53
0
Order By: Relevance
“…Unfortunately, 15 of the 25 patients in Kvols study received chemotherapy prior to the study; once again making it difÂźcult to interpret the antiproliferative effects of octreotide alone. Similarly, Anthony et al [24] reported four out of 14 patients had partial regression when treated with an escalating dose of octreotide (500± 2,000 mg q8h); however, one of the four responders received concomitant 5-FU therapy.…”
Section: Discussionmentioning
confidence: 83%
“…Unfortunately, 15 of the 25 patients in Kvols study received chemotherapy prior to the study; once again making it difÂźcult to interpret the antiproliferative effects of octreotide alone. Similarly, Anthony et al [24] reported four out of 14 patients had partial regression when treated with an escalating dose of octreotide (500± 2,000 mg q8h); however, one of the four responders received concomitant 5-FU therapy.…”
Section: Discussionmentioning
confidence: 83%
“…Evaluation of those 671 articles identified 12 primary clinical trials for inclusion in this review [22][23][24][25][26][27][28][29][30][31][32][33]. Another three articles for inclusion were selected based on the citations of these studies and/or recent reviews [34 -36].…”
Section: Octreotidementioning
confidence: 99%
“…Administration of a somatostatin analogue, such as octreotide, could be associated with antitumour activity in neuroendocrine neoplasm [69,70].…”
Section: Mediators Of Immune Effector Functionmentioning
confidence: 99%